Electron‐Rich Heptacyclic S,N Heteroacene Enabling C‐Shaped A‐D‐A‐type Electron Acceptors With Photoelectric Response beyond 1000 Nm for Highly Sensitive Near‐Infrared Photodetectors - Kuo‐Hsiu Huang; Bing‐Huang Jiang; Han‐Cheng Lu; Yung‐Jing Xue; Chia‐Fang Lu; Yung‐Yung Chang; Ching‐Li Huang; Su‐Ying Chien; Chih‐Ping Chen; Yen‐Ju Cheng (Advanced Science)
Abstract A highly electron‐rich S,N heteroacene building block is developed and condensed with FIC and Cl‐IC acceptors to furnish CT‐F and CT‐Cl, which exhibit near‐infrared (NIR) absorption beyond 1000 nm. The C‐shaped CT‐F and CT‐Cl self‐assemble into a highly ordered 3D intermolecular packing network via multiple π−π interactions in the single crystal structures. The CT‐F‐based organic photovoltaic (OPV) achieved an impressive efficiency of 14.30% with a broad external quantum efficiency response extending from the UV‐vis to the NIR (300–1050 nm) regions, outperforming most binary OPVs employing NIR A‐D‐A‐type acceptors. CT‐Cl possesses a higher surface energy than CT‐F, promoting vertical phase segregation and resulting in its preferential accumulation near the bottom interface of the blend. This arrangement, combined with the lower HOMO energy level of CT‐Cl, effectively reduces undesired hole and electron injection under reverse voltage. The PM6:CT‐Cl‐based organic photodetectors (OPDs) devices achieved an ultra‐high shot‐noise‐limited specific detectivity (Dsh*) values exceeding 1014 Jones in the NIR region from 620 to 1000 nm, reaching an unprecedentedly high value of 1.3 × 1014 Jones at 950 nm. When utilizing a 780 nm light source, the PM6:CT‐Cl‐based OPDs show record‐high rise/fall times of 0.33/0.11 µs and an exceptional cut‐off frequency (f‐3dB) of 590 kHz at −1 V.